MIF: Implications in the Pathoetiology of Systemic Lupus Erythematosus - Lang, Tali; Foote, Andrew; Lee, Jacinta P. W.; Morand, Eric F.; Harris, James (Frontiers in Immunology, 2015)
Macrophage Migration Inhibitory factor (MIF) was one of the earliest pro-inflammatory cytokines to be identified. Increasing interest in this cytokine in recent decades has followed the cloning of human MIF and the generation of Mif-/- mice. Deepening understanding of signalling pathways utilized by MIF and putative receptor mechanisms have followed. MIF is distinct from all other cytokines by virtue of its unique induction by and counter-regulation of glucocorticoids (GCs). MIF is further differentiated from other cytokines by its structural homology to specific tautomerase and isomerase enzymes and correlative in vitro enzymatic functions. The role of MIF in immune and inflammatory states, including a range of human autoimmune diseases, is now well established, as are the relationships between MIF polymorphisms and a number of inflammatory diseases. Here, we review the known pleiotropic activities of MIF, in addition to novel functions of MIF in processes including autophagy and autophagic cell death. In addition, recent developments in the understanding of the role of MIF in systemic lupus erythematosus (SLE) are reviewed. Finally we discuss the potential application of anti-MIF strategies to treat human diseases such as SLE, which will require a comprehensive understanding of the unique and complex activities of this ubiquitously expressed cytokine.